2021
DOI: 10.1186/s12870-021-03185-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide dynamic network analysis reveals the potential genes for MeJA-induced growth-to-defense transition

Abstract: Background Methyl jasmonate (MeJA), which has been identified as a lipid-derived stress hormone, mediates plant resistance to biotic/abiotic stress. Understanding MeJA-induced plant defense provides insight into how they responding to environmental stimuli. Result In this work, the dynamic network analysis method was used to quantitatively identify the tipping point of growth-to-defense transition and detect the associated genes. As a result, 146 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…Compared with mock plants, 461 differentially expressed genes (DEGs) and 301 DEGs were obtained from SA-treated plants and drm2 mutants from 28,959 expressing genes of Arabidopsis, respectively ( p < 0.05 ). These results are consistent with previous studies (Stroud et al 2014 ; Wang and Zhang 2021 ). Interestingly, 35 DEGs were shared by drm2 and SA treatment (Fig.…”
Section: Resultssupporting
confidence: 94%
“…Compared with mock plants, 461 differentially expressed genes (DEGs) and 301 DEGs were obtained from SA-treated plants and drm2 mutants from 28,959 expressing genes of Arabidopsis, respectively ( p < 0.05 ). These results are consistent with previous studies (Stroud et al 2014 ; Wang and Zhang 2021 ). Interestingly, 35 DEGs were shared by drm2 and SA treatment (Fig.…”
Section: Resultssupporting
confidence: 94%
“…In Arabidopsis, most vesicular trafficking to the plasma membrane is driven by SYP121/122 through their assembly with the R-SNAREs VAMP721/722 and the Qb+c-SNARE SNAP33 [ 57 ]. Wang and Zhang found that SYP121 and SYP122 are hub genes that play a key role in plant growth-to-defense transition [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Determining the stress-triggering events would require an alternative experimental approach as adult plants with constitutive transgene expression and pheromone production probably represent an already well-established defensive state. To better understand the events prompting the transition from the normal to stressed state and its major regulatory players ( Wang and Zhang, 2021 ), sampling after production initiation in a well-regulated and non-leaky inducible expression system (e.g. Garcia-Perez et al., 2022 ; Kallam et al., 2022 ) could give more conclusive insights.…”
Section: Discussionmentioning
confidence: 99%